2017
DOI: 10.1272/jnms.84.12
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Expression of Circulating TGF-β1 and BMP-2 Levels in Human Nonunion Long Bone Fracture Healing

Abstract: Background:The healing process of bone fracture requires a well-controlled multistage and sequential order beginning immediately after the injury. However, complications leading to nonunion exist, creating serious problems and costs for patients. Transforming growth factor-beta 1 (TGF-β1) and bone morphogenic protein 2 (BMP-2) are two major growth factors involved in human bone fracture healing by promoting various stages of bone ossification. In this study, we aimed to determine the role of these factors duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…Although the role of TGFβ signaling has been well established as an inhibitor of chondrocyte differentiation in the growth plate, its effect is also known to be highly temporal and dosage dependent especially during fracture healing . In patients with delayed fracture healing, TGFβ1 levels were found to be significantly modulated at various time points throughout healing . Treatments of fractures with different TGFβ ligands administered in various ways have been shown to have highly variable results depending on dosage, timing, and whether treatment was localized or systemic .…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of TGFβ signaling has been well established as an inhibitor of chondrocyte differentiation in the growth plate, its effect is also known to be highly temporal and dosage dependent especially during fracture healing . In patients with delayed fracture healing, TGFβ1 levels were found to be significantly modulated at various time points throughout healing . Treatments of fractures with different TGFβ ligands administered in various ways have been shown to have highly variable results depending on dosage, timing, and whether treatment was localized or systemic .…”
Section: Discussionmentioning
confidence: 99%
“…This should be taken into account when evaluating the results, since our study included patients of old and old age with the presence of concomitant diseases. In a study by Hara Y. et al (2017) showed that in the group of patients with normal fracture of the fracture, the maximum peak of TGF-β1 was ob-served 2 weeks after the injury, and in the group without adhesion, a delayed maximum peak was observed after 3 weeks [5]. It is also possible that the very presence of an implant leads to a local release of TGF-β by osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Як свідчать дослідження Y. Hara і співавт. [21], у групах пацієнтів із нормальним зрощенням перелому максимальну кількість TGF-β1 спостерігали через два тижні після травми, а серед пацієнтів без зрощення -через три. Також висловлено припущення, що власне наявність імплантата призводить до локального вивільнення TGF-β1 остеобластами [22].…”
Section: Taблиця 1 показники цитокінового статусу в сироватці крові пunclassified